2021
DOI: 10.1021/acs.macromol.1c02212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Star Architecture on the Dynamics of 1,4-cis-Polyisoprene under Nanometer Confinement

Abstract: The dynamics of a series of cis-1,4-polyisoprene stars located inside nanoporous alumina was investigated as a function of functionality, f (2 ≤ f ≤ 64), arm molar mass, M (2.6 ≤ M ≤ 13.5 kg•mol −1 ), and degree of confinement (0.01 ≤ 2R g /d ≤ 0.6; where R g is the radius of gyration and d is the pore diameter) by dielectric spectroscopy. In the bulk, dielectric spectroscopy revealed broadening of the chain modes with the increasing functionality. In addition, a slower dielectric process was found in the vici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…This effect for star polymers can be discussed with respect to a recent investigation of star PIs under confinement within the same pores (following long annealing). It was shown that star-shaped polymers with a large number of arms, present a higher affinity for adsorption in comparison to linear polymers and hence are more strongly affected by the confinement . Chain adsorption affected the dielectric strength of the chain modes that are unable to fluctuate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect for star polymers can be discussed with respect to a recent investigation of star PIs under confinement within the same pores (following long annealing). It was shown that star-shaped polymers with a large number of arms, present a higher affinity for adsorption in comparison to linear polymers and hence are more strongly affected by the confinement . Chain adsorption affected the dielectric strength of the chain modes that are unable to fluctuate.…”
Section: Resultsmentioning
confidence: 99%
“…The missing dielectric strength of the stars (blue arrow in Figure b) reflects the fraction of adsorbed arms on the AAO walls. It has been employed earlier by us to obtain an estimate of the thickness of the interfacial layer and further, to suggest some possible arm configurations next to the pores …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations